Weight Estimation Method In Emergency Department In Malaysia: Is Broselow Tape (Bt) Reliable? - Sahar, MA; Nor, ATM; Zakaria, MI; Norsham Juliana Nordin (Penerbit UTM Press, 2024)
Indexed by WOS/ Scopus